Pengaruh Gaji Terhadap Kepuasan Kerja Karyawan di Lesehan Jetpur Sengkang - Syahida; Muria Maulana; Indra Heri Rukmana (Yayasan Pengembangan Sumber Daya Insani Lamaddukelleng, 2025)
Human resources are an important asset in the service industry, including the culinary sector, where employee job satisfaction is a determining factor in service quality and business sustainability. This study aims to analyze the effect of salary on employee job satisfaction at Lesehan Jetpur Sengkang. The research method used is quantitative with a survey approach, where primary data was obtained through distributing questionnaires to 30 respondents and analyzed using validity and reliability tests, simple linear regression, t-test, F-test, and coefficient of determination. The results show that salary has a positive and significant effect on employee job satisfaction, indicated by a regression coefficient value of 0.172 and a significance level of 0.000 (<0.05). The coefficient of determination (R²) of 0.57 indicates that 57% of the variation in job satisfaction is explained by salary factors, while the rest is influenced by other variables outside the model. These findings confirm that a fair, transparent, and workload-appropriate salary system can increase employee motivation, loyalty, and performance. The practical implication of this study is the importance of evaluating compensation policies to create a more productive and sustainable work environment in the culinary industry